Potential use of coal ash as growing media: Effect on the plant’s growth and future estimation for land reclamation - Sri Suhartini; Reny Nurul Utami; Evi Kurniati; Laura Listy Simamora; Catherine Abigail Utomo Putri; Baskorohadi Supartono; Lynsey Melville (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Coal ash, such as fly ash (FA) and bottom ash (BA) is mostly generated from a Coal-fired Steam Power Generation (PLTU) process. An increase in the number of PLTUs in Indonesia is proportional to the high volume of FA and BA generated, causing adverse environmental impacts if not properly treated. Various studies have highlighted the potential valorization of FA and BA, including building materials, cement ingredients, concrete, and growing media. This study aimed to evaluate the potential use of FA and BA as a growing media and to explore the potential future application for reclamation of heavy-metal-contaminated (or ex-mining) land. The results showed that composting FA with blackwater sludge (BWS) and rice straw (RS) produced compost that complied with the targeted standard. The addition of FA, BA, and composted FA in the growing media impact the growth and Zn adsorption ability of the dwarf elephant grass (Pennisetum purpureum cv. Mott). However, the composted FA has superior performance in general as a growing media. The future estimation of the application FA and BA combined with domestic waste (blackwater and greywater) for reclamation of ex-mining land is proposed. By integrating the phytoremediation ability of the grass plants and the biorefinery approach, the proposed future estimation may provide a sustainable valorization pathway of FA and BA for heavy metal-contaminated or ex-mining land reclamation. Thus, transforming FA and BA as a component of growing media could reduce the potential risk of heavy metals distribution into the food chain and the surrounding environment.